Perception towards the importance of mobile application in Malaysia rural community / Nur Aishah Husin - Husin, Nur Aishah (2010)
Nowadays mobile technology becomes more famous among Malaysian community. Rural communities are the people that need to have access to the most necessary services and to deliver suitable service to rural community, mobile technology are the most suitable devices to them. Most of mobile application nowadays is very technology focused and task oriented. Usually these mobile applications were develop according to the specific technology and purpose. As a result, these applications are less useful and difficult to use by less technical user. This study introduces the most suitable mobile application that can be used by rural community according to their nature of work and activity. The aim of this research is to determine the pattern of importance of mobile application according to the rural community activity, and the objective of this study is to identify the kind of mobile application that is suitable to rural community by secondary data, to investigate the importance of mobile application suitable for rural context in Malaysia by empirical study and to propose a table of importance of mobile application for rural context in Malaysia. An investigation using guided interview approach was performed to obtain subject responses to the addressed questions. The result shows that the kind of mobile application suitable to rural community could be grouped into difference importance level. The outcome will benefit the mobile application developer to strategize the kind of mobile application that will be useful to the community and these increase the usage and sustainable of IT. This study is being done at Bukit Besar Kulai, located at Johor Baharu Malaysia where most of the community works in oil palm plantation.